Pengaruh Human Relation Dan Etika Kerja Terhadap Prestasi Kerja Pegawai Pada Badan Penanggulangan Bencana Daerah Kota Sibolga - Putri Tasya Regina Situmeang; Zafril Abdi Nasution; Andrian Irsyan (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
Work performance achievement in an organization is strongly influenced by human relations and employees’ work ethics. This study aims to analyze the partial and simultaneous effects of human relations and work ethics on employee performance at the Regional Disaster Management Agency of Sibolga City. The research method used is a quantitative descriptive approach with a sample of 70 respondents. Data were analyzed using multiple linear regression analysis. The results show that human relations and work ethics have a significant effect on employee performance, contributing 62.3%. Simultaneously, both variables significantly affect performance, as indicated by the F-value of 57.961, which is higher than the F-table value of 3.13. Partially, human relations have a significant effect with a t-value of 3.182, while work ethics has a more dominant effect with a t-value of 6.991. The regression model indicates a positive relationship, meaning that improvements in human relations and work ethics will enhance employee performance.